Statistical analysis of ethnic wage gaps in New Zealand (New Zealand Government, The Treasury, 2018)
This paper estimates the contribution of differences in measured personal and job characteristics to New Zealand's ethnic wage gaps. There are substantial and persistent gaps between the average hourly wages of Pākehā, Māori and Pacific employees. Survey estimates published by Statistics NZ show that the average hourly wage earned by Māori employees was 82% of the average hourly Pākehā wage in 2017, while the average wage earned by Pacific employees was 77% of the average Pākehā wage. The purpose of the paper is to investigate the extent to which ethnic group differences in demographic, productivity-related or job characteristics may be contributing to the ethnic pay gaps. Treasury has produced this paper as one of its contributions to He kai kei aku ringa, the previous Government's Māori economic development strategy.
Keywords: 330